A 10 GHz oversampling delta modulating analogue-to-digital converter implemented with hybrid superconducting digital logic - Fourie, Coenrad Johann (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2001.